Semantic And Pragmatic Characteristics Of Lexical Contamination In Modern French - Safarova Umida Aliaskarovna (Genius Journals, 2022)
Language, following the philosophy and dynamics of life, is in a state of constant transformation. At the same time, the linguistic phenomena themselves, as a rule, are due not only to internal, but also to external reasons, namely social and ideological transformations, or, in other words, changes in the life of society. Changes in language, their social causes and consequences are one of the most interesting and topical topics of modern linguistics.
Keywords: Methods of syntactic contamination; elements; contaminant; dynamics